Insights into the efficacy of golimumab plus methotrexate in patients with active rheumatoid arthritis who discontinued prior anti-tumour necrosis factor therapy: post-hoc analyses from the GO-AFTER study. Issue 10 (29th July 2013) - Smolen, Josef S; Kay, Jonathan; Matteson, Eric L; Landewé, Robert; Hsia, Elizabeth C; Xu, Stephen; Zhou, Yiying; Doyle, Mittie K
Abstract : Objective: Evaluate golimumab in patients with active rheumatoid arthritis (RA) and previous tumour necrosis factor-α (TNF) inhibitor use. Methods: Patients (n=461) previously receiving ≥1 TNF inhibitor were randomised to subcutaneous injections of placebo, golimumab 50 mg or golimumab 100 mg q4 weeks. Primary endpoint (≥20% improvement in American College of Rheumatology (ACR20) criteria at week 14) findings have been reported for all patients in the trial. Reported herein are further assessments of efficacy/safety among patients receiving golimumab+methotrexate (MTX). Results: Among efficacy-evaluable patients who received MTX at baseline, more receiving golimumab+MTX (n=201) than placebo+MTX (n=103) achieved ACR20 (40.8% vs 14.6%), ACR50 (20.9% vs 3.9%), and ACR70 (11.4% vs 2.9%) responses at week 24. Among the 137 patients who had received only one prior TNF inhibitor (adalimumab, n=33; etanercept, n=47; and infliximab, n=57), week 24 ACR20 rates were 30.3%, 46.8% and 50.9%, respectively, and thus lowest among those who previously used adalimumab. ACR20 response rates were 44.5% (61/137), 36.2% (17/47) and 23.5% (4/17) among patients who had received one, two or three TNF inhibitors, respectively. Adverse event (AE) rates were comparable across type/number of prior anti-TNF agents, but appeared somewhat higher among patients who discontinued previous TNF inhibitor(s) due to intolerance (37/49, 75.5%) versus lack of efficacy (LOE, 113/191, 59.2%). Conclusions: Patients with active RA previously treated with ≥1 TNF inhibitor had clinically relevant improvement with golimumab+MTX, which appeared somewhat enhanced among those who received only etanercept or infliximab as their prior TNF inhibitor. Golimumab+MTX safety appeared similar across patients, regardless of TNF inhibitor(s) previously used, with fewer AEs occurring among patients who discontinued prior therapy for LOE.